2016
DOI: 10.1097/brs.0000000000001286
|View full text |Cite
|
Sign up to set email alerts
|

Association of Calcium and Phosphate Balance, Vitamin D, PTH, and Calcitonin in Patients With Adolescent Idiopathic Scoliosis

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
52
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 26 publications
11
52
1
Order By: Relevance
“…It is a multifactorial disease with uncertain primary etiology and pathogenesis [24]. The potential role of Vitamin-D in the developing adolescent scoliosis is recently being considered [25], [26]. The results of the present study provide adequate evidence of a positive relation between VDD (<25 nmol/L) and clinically detected scoliosis in adolescents.…”
Section: Discussionsupporting
confidence: 55%
“…It is a multifactorial disease with uncertain primary etiology and pathogenesis [24]. The potential role of Vitamin-D in the developing adolescent scoliosis is recently being considered [25], [26]. The results of the present study provide adequate evidence of a positive relation between VDD (<25 nmol/L) and clinically detected scoliosis in adolescents.…”
Section: Discussionsupporting
confidence: 55%
“…Vitamin D is a major factor involved in the bone growth; if deficient during first years of life, it is associated with poor skeletal mineralization, leading to a wide variety of skeletal deformities. While some studies have reported that vitamin D deficiency is frequent in patients with AIS, the modality by which vitamin D influences scoliosis is not established [11].…”
Section: Introductionmentioning
confidence: 99%
“…In most of such cases, the fractured bones are pieced together in their native format and incubated at fairly warm temperatures (40-50°) after wrapping with plants leaves such as wild Ocimum gratissimum [26,31] such fractures often healed up after few days (7-21 days). Further studies on this traditional method of fixing fractures using broken/fractured chicken legs have confirmed the possible efficacy of this method in the local treatment of fractures [27,32]. Although, most of these methodologies are empirical, the possibility of enhanced osteoblastic activity due to increased vitamin D supplementation from the leaves cannot be totally ruled out.…”
Section: Fixing Of Fracturesmentioning
confidence: 96%